Case report: Low-grade myofibroblastic sarcoma resembling lymphoma on 18F-FDG PET/CT - Zhang, Huan; He, Liu; Hu, Bin; Zhang, Xiaoming; Zheng, Lichun (Frontiers in Oncology, 2023)
Low-grade myofibroblastic sarcoma is a rare malignant tumor that arises from mesenchymal tissue and affects the head (particularly the tongue and oral cavity) and neck. It is characterized by local recurrence, with metastases being uncommon. We present a 72-year-old man who initially complained of a painless and progressive mass in the right inguinal region and came for consultation, and a malignant tumor was suspected based on the clinical and pelvic MRI manifestations. The 18F-FDG PET/CT revealed that the multiple lesions were located in the mediastinum, retroperitoneum, pelvis, and inguinal lymph nodes; hence, lymphoma was considered to be a combination of the symptoms. However, the histology of the ultrasound-guided puncture indicated low-grade myofibroblastic sarcoma. The patient was next administered chemotherapy, but the lesions did not undergo remission.